A Correction to the article "Geo-center movement caused by huge earthquakes" by Wenke Sun and Jie Dong. (July 2015) - Zhou, Jiangcun; Sun, Wenke; Dong, Jie
Abstract: Sun and Dong (2014) studied the co-seismic geo-center movement using dislocation theory for a spherical earth model. However, they incorrectly considered the maximum vertical co-seismic displacement as the rigid geo-center motion (i.e., they did not separate the rigid shift and elastic deformation). In this paper, we correctSun and Dong (2014) by using a new approach. We now define the geo-center motion as a shift of the center of figure of the Earth relative to the center of mass of the Earth. Furthermore, we derive new formulas to compute the co-seismic geo-center and inner core's center movements caused by huge earthquakes. The 2004 Sumatra earthquake and the 2011 Tohoku-Oki earthquake changed the geo-center by 1–4 mm and about 2 mm, respectively, and caused the inner core's center to displace by about 0.05 mm and 0.025 mm, respectively.